Strategi Mempertahankan Eksistensi Profesi Akuntan Syariah di Era Revolusi Industri 5.0 - Eny Latifah; Yusuf Yusuf (Jurnal Ekonomi Manajemen Akuntansi, 2025)
The aim of this research is to show how to maintain the existence of the sharia accounting profession in the era of industrial revolution 5.0 in Indonesia. The research method is qualitative with the type of literature study. The results of the research are that strategies for maintaining the existence of the sharia accounting profession in the era of the industrial revolution 5.0 in Indonesia can still be maintained in various ways, namely: (1) Designing assignments that are non-routine and unstructured, where the performance of judgment and wisdom really requires a mindset. humans and special skills that can only be done by humans and cannot be done by technology such as robots or other technological tools; (2) Using Technical Skills and Ethics (TEQ) by understanding relevant technology and acting with ethics and a sense of responsibility not only to stakeholders in the world but to Allah SWT in the afterlife; (3) The duties of sharia accountants as supervisors of sharia-based industries provide great opportunities for sharia accountants to maintain their existence (4). There is no need to worry about the impending threat of industrial revolution 5.0 in the sharia accounting profession because technological developments cannot be prevented. However, what must be done is to adapt and improve the quality of accounting education by providing services both virtual and conventional and (5) Technology will never be able to replace the role of ethics and Islamic religious values ​​and principles in business concepts or transactions based on Islamic sharia.